Meningkatkan Kemampuan Kognitif Anak melalui Pembelajaran Sains Gelembung Sabun Belalai Gajah di TK Fathul Huda - Alifah, Aqila Nur Insan (AS-SABIQUN, 2024)
This study was conducted to improve children's cognitive abilities through science learning, namely elephant trunk soap bubbles with experimental methods. This study aims to observe the initial condition of early childhood cognitive abilities before being given learning activities using the science experiment method. The method used is the PTK (Classroom Action Research) method, the subjects used are all group B children at Fathul Huda Kindergarten. The data collection techniques used are observation by looking at the condition of the class children to be studied, interviews conducted with children and also with class b teachers and documentation conducted when learning is taking place. The data analysis technique used is qualitative. The results of the study showed that this elephant trunk soap bubble learning can improve children's cognitive abilities. Thus it can be concluded that science learning through elephant trunk soap bubble experiments is quite effective in improving cognitive abilities of early childhood and the cognitive development of children is also higher than before.